The Social and Demographic Characteristics of Cohabiters in Australia - Buchler, S; Haynes, M; Western, M; Baxter, Janeen (My University, 2009)
In this paper, variations in types of cohabiters were examined, emphasising the importance of understanding cohabiters as a heterogeneous group. The authors devised a typology that divides cohabiters into four groups, by intention to marry and previous marital status. They then compared these groups to one another and to married people using a range of demographic and attitudinal indicators, using data from the first wave (2001) of the Household, Income and Labour Dynamics in Australia (HILDA) survey. The authors found evidence of significant variation among cohabiters and between cohabiters and married persons. It was concluded that the recent rise in cohabiting relationships has led to significant diversity in the types of people choosing to cohabit rather than marry, and is a reflection of fundamental changes in patterns of family formation and the changing status of marriage in the life course.
Family Matters
Keywords: Relationships; Relationships -- Cohabitation; Families and relationships; Relationships; Cohabitation; Families and relationships